An Interpretation of the Paratexts of Three Kingdoms Translated by Moss Roberts - Fang, Jia; Hou, Yan Fang (International Journal of Humanities and Education Development (IJHED), 2021)
Paratext is an inseparable part of translation. It can reveal what the translated text cannot explain and is of great significance to translation studies. This article uses the English translation of the Romance of the Three Kingdoms by American Sinologist Moss Roberts as the research object, and attempts to interpret Roberts’ translation views and translation promotional factors through peritext, such as the cover, acknowledgments, annotations and postscripts, and epitext, such as interviews, reviews and other external paratexts. It is found that Roberts’ translation motivation of the Romance of the Three Kingdoms is mainly to spread Chinese culture by literature. He always keeps readers in his heart and has a strong reader consciousness. Therefore, he mainly adopts domestication strategies and uses a lot of annotations to make the readers better understand the meaning and Chinese culture. Secondly, the author found that the translator’s own erudite and rigorous attitude, the cooperation of Chinese and foreign publishing houses, and the evaluation of well-known sinologists all promoted the spread and acceptance of the Romance of the Three Kingdoms. This study interprets Roberts’ translation view and the promotional factors of the translation from the paratext, hoping to help comprehensively and objectively evaluate the value of Roberts’ translation, and at the same time promote the in-depth and development of translation studies from the perspective of the paratext.